Community Perception of Homegarden Utilization Can Support Food Diversification in Tambakrejo Village Jombang - Ahmad Nurfaizin; Anggi Indah Yuliana; Nurul Aini; Nerisa Agnesia Widiyanto (AGARICUS: Advances Agriculture Science & Farming, 2022)
Food production has decreased every year, due to the conversion of agricultural land and population growth that continues to increase. Therefore, the yard is one solution to maintain food availability and even food diversification in the family. This study aimed to measure the level of public perception of the use of homegarden in supporting food diversification in Tambakrejo Village, Jombang District, Jombang Regency. This type of research is a qualitative research with descriptive statistical analysis. The sample in this study amounted to 100 respondents with a questionnaire in the form of a Likert scale. The results obtained in this study indicate that the community perception of Tambakrejo Village towards the processing of homegarden is in the low category, the community perception of Tambakrejo Village on the benefits of homegarden utilization in the low category, the community perception of Tambakrejo Village on food diversification is in the medium category, and the community perception of Tambakrejo Village on the sustainability of homegargen processing is categorized high.